The Effects of Implementation Quality of a School-Based Social and Emotional Well-Being Program on Students' Outcomes - Katherine Dowling; Margaret M. Barry (MDPI AG, 2020)
School-based social and emotional learning (SEL) programs can be effective in producing positive outcomes for students. However, when the implementation quality is poor, these programs often lose their effectiveness and fail to produce the expected positive outcomes. The current study evaluates a school-based SEL program for 15-18-year-olds in Ireland by determining the impact of implementation quality on program outcomes. The study also examines the effects on outcomes of different implementation dimensions including Dosage, Adherence, Quality of Delivery, and Participant Responsiveness. Employing a cluster randomized controlled trial design, this study collected student outcome data (n = 675) from 32 disadvantaged schools across three time points (pre-, post-, 12-month follow-up) and compared these data across three treatment groups (high-implementation, low-implementation, and control). Linear mixed models (LMM) were used to determine the relationships between the implementation data and student outcome data longitudinally. The findings revealed that the positive effects of the program were only observed with the high-, but not the low-implementation group (reduced suppression of emotions (p = 0.049); reduced avoidance coping (p = 0.006); increased social support coping (p = 0.009); reduced levels of stress (p = 0.035) and depressive symptoms (p = 0.025). The comparison of implementation dimensions revealed that only Quality of Delivery had a significant effect on all of the tested outcomes. This study highlights the importance of high-quality implementation in producing positive outcomes and supports the need to evaluate implementation using multiple dimensions.